Transformação química de produtos naturais como estratégia de produção de compostos bioativos: triterpeno 3β,6β,16β-tri-hidroxilup-20(29)-eno isolado de Combretum leprosum - Silva Filho, Carlos José Alves da (2020)
The species Combretum leprosum Mart. (Cobretaceae), with wide dispersion in the Northeast region of Brazil, is a shrub popularly known as Mufumbo, Mofumbo or Cipoaba. It is widely used in folk medicine as a healing agent, sedative, antidiarrheal, expectorant, in rashes and hemostatic agent. The main isolated substance of C. leprosum is triterpene 3β,6β,16β-tri-hydroxylup-20(29)-eno (CL-1), which has various biological activities such as leishmanicide, anti-inflammatory, antimicrobial, antinociceptive, healing and anticancer. This work describes the isolation of this metabolite and the production of the semi-synthetic derivatives dehydrated (CL-P1), triacylated (CL-P2), diacylated (CL-P2A), oxidized (CL-P3), hydrogenated (CL-P5), hydrazine (CL-P6) and oxime (CL-P8 e CL-P9), as well as the evaluation of their cytotoxic and analgesic activity. All compounds had their structures determined by spectrometric methods (MS, IR, uni and two-dimensional NMR). The CL-P1, CL-P2, CL-P2A, CL-P5, CL-P6, CL-P8 e CL-P9 derivatives are unpublished. With the exception of the acylated (CL-P2, CL-P2A) and oximes (CL-P8 e CL-P9) derivatives, all others had cytotoxic activity against four human tumor cell lines (HL-60 (Leukemia), HCT-116 (Human colon), PC-3 (Prostate) and SNB-19 (Gliobastoma)) tested. The natural product (CL-1) and the hydrogenated (CL-P5) derivative presented cell growth inhibition percentage above 75% in all strains, while the dehydrated derivative (CL-P1) was active only in the HCT-116 strain. The natural metabolite and the hydrogenated derivative showed an IC50 variation of 4.66 - 8.93 and 3.78 at 13.61 µg / mL, respectively. The triacylated derivative (CL-P2) showed antinociceptive activity and absence of toxicity in murine and human fibroblasts at 0,1 µg/Kg. These results show that the studies of semisynthesis in secondary metabolites are an important tool in the development and therapeutic enhancement of new drugs.